Pengaruh Likuiditas terhadap Harga Saham PT. Jasa Marga (Persero) Tbk - Lestari, Nadia; Munandar, Aris (Universitas muhammadiyah palembang, 2020)
This study aims to determine whether there is a significant effect between Liquidity on Share Prices at PT. Jasa Marga (Persero) Tbk. Liquidity as the independent variable while the Stock Price as a Bound Variable. The cause of Jasa Marga's share price decline is because the company will enter an expansion cycle. This increase was due to the increase in debt to the Bank to finance land bailouts to the Subsidiaries which was quite high. This condition is considered to have influenced the downward trend in share prices of PT. Jasa Marga (Persero) Tbk. This type of research is associative using secondary data, the population used is financial statement data for 12 years starting in 2007 - 2018 while the sample in this study is financial statement data for 5 years, namely in 2014 - 2018. The sampling technique using Purposive Sampling. Collection techniques using documentation and study of literature. Data analysis techniques using Current Ratio, Simple Linear Regression Analysis, Simple Correlation Coefficient, Simple Determination Coefficient, and One-Sample t-Test Analysis. The results of the Current Ratio value have fluctuated for 5 years, but losses have increased very high in 2015, 2016, and 2018. Current Ratio has a significant effect on the Stock Price